Challenges and opportunities in the digital transformation of Brazilian SMEs (International Seven Journal of Multidisciplinary, 2024)
The digital transformation of Brazilian SMEs is essential to maintain competitiveness in the current market, especially after the challenges imposed by the COVID-19 pandemic. Adopting digital technologies enables these businesses to better connect with customers, increase operational efficiency, and innovate quickly. However, the transition faces significant obstacles, such as a lack of skills and resistance to change. With well-planned strategies, digitalization can bring great economic benefits and sustainable growth in the future.